Sàng lọc và tuyển chọn một số dòng lúa chỉnh sửa gen GS3 bằng CRISPR/Cas9 - Tien, Dung Nguyen (2025)
Screening 41 GS3 putative-edited T0 rice lines of Bac Thom 7 cultivar by PCR, obtained 38 lines carrying the gene encoding Cas9 protein. Sequencing analysis identified two lines D1 and D25, having two nucleotides T, C deleted at positions 127 and 128 as compared to the original sequence. The target mutant lines expressed a significant variation in grain size, from 0.68 to 0.97 cm in length and 0.21 to 0.27 cm in width, of which 15 lines exhibited their larger grain size (from 0.86 to 0.97 cm), and 4 lines were smaller than the control. The 1,000-grain weight ranged from 13.6 to 22.6 g. In which, ten lines showed a higher 1,000-grain weight of 19.22- 22.6 g than the control of 17.9 g. This indicated that GS3 gene mutation has increased grain size in Bac Thom 7 cultivar. However, there is still a need to further analyse the function of mutant lines as well as evaluate other agro-biological characteristics of these promising rice lines.